Living Qur’an, Niqab, and Islamic Law: A Study at Mambaush Sholihin Islamic Boarding School, Gresik, East Java - Toriquddin, Moh; Faizin, Nur; Hamidah, Tutik; Hamdan, Ali; Muhammad, Muhammad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
Two impressions emerging from wearing a niqab (face veil), i.e., piety and radicalism, are deeply embedded in public perception. The obligation to wear the niqab for female students at an Islamic boarding school known to be moderate and cultural, such as the Mambaush Sholihin Islamic Boarding School, is an interesting issue to study. In this current study, the empirical legal method was used, based on the theory of the living Qur’an and Islamic law. Data collection techniques included in-depth interview, literature review, and focus group discussion. The findings reveal that in the opinions of the Islamic boarding school caretakers, the use of the niqab at Mambaush Shalihin does not lead to an exclusive attitude, but rather to code of conduct, that limits the interaction between men and women. However, some students respond to this conduct differently and they view it as a form of coercion, giving rise to an attitude of resistance expressed when they are outside the school, whereas others still prioritize an attitude of obedience and submission to the kyai. On the other hand, some people in the public perceive this as a form of change in the Islamic boarding school towards radicalism while others believe that the school remain on the principles of the moderate teachings of Ahl Sunnah wal Jamaah. In practice, wearing the niqab at Mambaush Shalihin is a form of the Living Qur’an in relation to the command to cover the awrah(private parts) for women. Meanwhile, according to Islamic law, the law on wearing the veil is different among the scholars of the four schools of thought. This article argues that the use of the veil in Islamic boarding schools is not affiliated with a particular madhhab but rather aims to discipline female students who study in the same room as male students. This is indicated by the non-obligation to wear any face veil for female students who have not yet studied in college, i.e., junior and senior high school levels.